(untitled) (Scottish Historical and Archaeological Internet Reports, 2010)
This chapter described the main archaeological features encountered during the excavation, and the artefactual and environmental evidence where appropriate. The results are prefaced by a summary of the main archaeological findings. At the end of the chapter is a brief discussion of how the archaeological results shed light on the main research questions posed at the beginning of the project.